1831. Point Prevalence and Epidemiology of Antimicrobial Use in US Nursing Homes, 2017. (26th November 2018) - Thompson, Nicola D; Brown, Cedric J; Eure, Taniece; Penna, Austin; Bamberg, Wendy; Barney, Grant; Barter, Devra; Clogher, Paula; Desilva, Malini; Dumyati, Ghinwa; Epson, Erin; Frank, Linda; et al.
Abstract: Background: The role of nursing homes (NH) in transmission of antimicrobial-resistant (AR) organisms is of growing concern. AR control requires evidence-based NH stewardship interventions; however, data on antimicrobial use (AU) from US NHs are scant. In the absence of other AU surveillance approaches, NH prevalence surveys can generate essential data, including rationale and indication. In 2017, an AU prevalence survey was conducted through the CDC's Emerging Infections Program (EIP) to determine the prevalence and epidemiology of AU in NH residents. Methods: NHs from California, Colorado, Connecticut, Georgia, Maryland, Minnesota, New Mexico, New York, Oregon, and Tennessee were randomly selected to participate in a 1-day AU point prevalence survey; participation was voluntary. For NH residents receiving antimicrobial drugs (AD) at the time of the survey, EIP staff reviewed available medical records to collect the AD route, rationale, and infection site(s). AD were categorized using the World Health Organization Anatomical Therapeutic Chemical classification system. Data were analyzed in SAS 9.4. Results: Of 15, 295 residents in 161 NHs, 1, 261 (prevalence 8.2%, 95% confidence interval 7.8%-8.7%) received ≥1 AD at the time of the survey (AD range 1–4/resident). Of 1, 452 total ADs, 77% were administered for treatment of an active infection, 19% for prophylaxis, 3% for noninfectious reasons, and no rationale documented in 1%. Most AD (80%) were administered by the oral/enteral route and most (87%) were antibacterials. The three most common infection sites were urinary tract (29%, of which 1/4 was for prophylaxis); wound, cellulitis or soft tissue (20%); and respiratory tract (14%). Among the 1, 268 antibacterials (figure), fluoroquinolones (15%), combination penicillins (8%), third-generation cephalosporins (8%), and glycopepetides (5%) ranked among the top 10 classes in use. Conclusion: This large-scale prevalence survey provides insight into AU in US NHs. On a given day, approximately 1 in 12 NH residents was receiving ≥1 AD. Notably, 30% of AD were administered for UTI, and AD in classes recommended for stewardship intervention were common. These findings highlight areas for evaluation to identify unnecessary use in NH. Prevalence survey data are important to inform and track the impact of stewardship interventions. Disclosures: All authors: No reported disclosures.